Generative artificial intelligence in education: a bibliometric analysis: - Xavier Muniz, Aline Barbosa (2026)
This article explores the use of Generative Artificial Intelligence (GenAI) in education through a bibliometric and qualitative approach. The study identifies emerging themes and highlights GenAI’s impact in educational contexts. Data from the Scopus database were analyzed using VOSviewer, Gephi, and Bibliometrix to examine keyword co-occurrences, driving themes, and highly cited articles. Findings were grouped into three main clusters: ChatGPT, Generative AI, and Technological Education, addressing issues such as ethics, academic integrity, and digital transformation. The analysis shows that while GenAI offers opportunities like improved accessibility and educational efficiency, it also raises concerns about bias, privacy, and the decline of critical thinking. This study contributes to understanding GenAI’s implications for education, offering insights for future research and practice.